Recombinant human endostatin combined with chemotherapy for advanced squamous cell lung cancer: a meta-analysis - Feng, Li (World J Surg Oncol, 2021)
BACKGROUND: This paper aims to compare the efficacy and safety of recombinant human endostatin combined with chemotherapy in patients with squamous cell lung cancer (SqCLC). METHODS: We searched the Cochrane Library, PubMed, Embase, CNKI, Wanfang database, Metstr, VIP, and others and manually searched books and magazines until 2019 for articles about the efficacy and safety of recombinant human endostatin combined with chemotherapy in patients with SqCLC. A second search was conducted on the review literature. According to the criteria of the literature screen, the relevant randomized controlled trials (RCTs) and nonrandomized controlled trials (non-RCTs) of recombinant human endostatin combined with chemotherapy and chemotherapy alone in the treatment of SqCLC were included. After the data were extracted and analyzed, RevMan 5.3 software was used for meta-analysis for the outcome indicators. Then, heterogeneity tests and sensitivity analyses were carried out, and the publication bias of this study was tested in Stata 13.0 software. Six RCTs and eight non-RCTs were included. In total, 821 patients with SqCLC were included. RESULTS: The response rate (RR) was 2.12 (95% CI: 1.57–2.85, p < 0.00001). The disease control rate (DCR) was 2.38 (95% CI: 1.70–3.32, p < 0.00001). The difference between the two groups was statistically significant. Regarding safety, the incidence rates of the adverse reactions cardiotoxicity, leukopenia, thrombocytopenia, and gastrointestinal reactions were not significantly different between the two groups (OR = 1.70, 95% CI: 0.79–3.68; OR = 0.93, 95% CI: 0.61–1.42; OR = 1.08, 95% CI: 0.71–1.64; OR = 0.86, 95% CI: 0.56–1.30, respectively). CONCLUSION: The combined treatment had a better therapeutic effect than chemotherapy alone. It did not increase the incidence of adverse reactions in the course of treatment.